The Effect of Methadone Maintenance Treatment on Health Psyche and Having Hope in Drug Addicted Persons - Aazam Shahmoradi; Mohammad ali Mohammadifar; Mohammad khazem Fakhri (Drug Control Headquarters, Research and Education Office, 2011)
Objective: the aim of the present study was the survey of methadone maintenance treatment on health psyche and having hope in drug addicted persons. Method: the sample population was 60, 30 people were under Methadone Maintenance Treatment and 30 people who were waiting to receive methadone maintenance treatment. The range of their age was about 19-55 who were selected by in-hand sampling, according to Minoudasht city clinics. Sample group surveyed by general health and Sneider questionnaire. Findings: the results showed that between health psyche and being hopeful in people who are under methadone maintenance treatment and people who were waiting to receive methadone maintenance treatment, there is a significant meaning. Conclusion: methadone maintenance treatment can be counted as one of the ways to be used in quitting drug addiction.